Betawi Ethnic Family Communication Patterns in Building Awareness of the Importance of Higher Education for Daughters - Maulina Larasati Putri; Aminah Devina Fajri; Ayu Priana (Universitas Ahmad Dahlan, 2021)
Family is one of the most important aspects in human life and is also the first environment that will be an example for every individual, especially for a child. Family is the first place where children form their potential. The first education a child gets also comes from the family. In Indonesia, which has a variety of cultures, of course, has differences in communication, especially communication within the family. The ethnicity we examined in this study was the Betawi ethnicity, where previously the Betawi people thought that education for daughters was not an obligation but as the development of the cultural age also developed over the course of time we found many women from the Betawi ethnicity were able to teach learners in higher education. This is also influenced by the mindset instilled by the Betawi ethnic family through the instilled family communication pattern. Â In this study, researchers are interested in knowing how the communication patterns of Betawi ethnic families in building awareness of the importance of higher education for daughters. The method used in this research is a quantitative method by collecting data using a questionnaire which is distributed to 30 respondents. The respondents of this study were daughters from the Betawi ethnicity. The results of this study indicate that the Betawi ethnic family tends to apply the balanced split pattern and the unbalanced split pattern, in which the balanced split pattern prioritizes equality in roles and balanced tasks for each family member. Meanwhile, the unbalanced split pattern applies the opposite. This communication pattern is not balanced, and one of the dominant family members in the family.Â Â